2020
DOI: 10.1186/s42506-019-0032-7
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and associated factors of internet addiction among young adults in Bangladesh

Abstract: Background: In the last decades, the use of internet has increased many folds, and internet addiction has become a severe public health issue around the world. This study aimed to determine the prevalence of internet addiction among young adults (19-35 years) in Bangladesh and to identify factors associated with it. Methods: A total of 454 participants were selected from three administrative divisions of Bangladesh using multistage cluster sampling for this cross-sectional study. A self-reported questionnaire … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
112
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(144 citation statements)
references
References 29 publications
12
112
2
Order By: Relevance
“…Another study revealed no correlation between Internet addiction and the type of device used to access the Internet (Salam, Alrowaili, Albedaiwi, Alessa, & Alfayyadh, 2019). A study conducted in Bangladesh found that students who accessed the Internet via computer had significantly higher Internet addiction scores (Hassan, Alam, Wahab, & Hawlader, 2020). This difference may be associated with the presence of regional‐cultural differences as well as the Internet access' having become easier and more widespread depending on the data collected at different times.…”
Section: Discussionmentioning
confidence: 99%
“…Another study revealed no correlation between Internet addiction and the type of device used to access the Internet (Salam, Alrowaili, Albedaiwi, Alessa, & Alfayyadh, 2019). A study conducted in Bangladesh found that students who accessed the Internet via computer had significantly higher Internet addiction scores (Hassan, Alam, Wahab, & Hawlader, 2020). This difference may be associated with the presence of regional‐cultural differences as well as the Internet access' having become easier and more widespread depending on the data collected at different times.…”
Section: Discussionmentioning
confidence: 99%
“…Poor dietary habits such as carbonated soft drinks and fast food consumptions have been reported to be related to IA among adolescents [ 21 , 22 ]. A recent study among young adults in Bangladesh also suggested that IA was significantly higher among respondents who had a smoking habit or did not involve in a considerable amount of physical activity [ 23 ]. However, studies focusing on IA and lifestyle among adolescents are still lacking in Malaysia.…”
Section: Introductionmentioning
confidence: 99%
“…Internet addiction among young Bangladeshi adults: critical commentary on Hassan et al (2020) Mark D. Griffiths 1* and Mohammed A. Mamun 1,2 Dear Editor,…”
mentioning
confidence: 99%
“…We were very interested to read the paper by Hassan et al [1] examining the prevalence and associated factors of internet addiction (IA) among young Bangladeshi adults. However, there are a number of issues of concern that we would like to raise.…”
mentioning
confidence: 99%
See 1 more Smart Citation